Factors influencing sexual risk behaviours among rural adolescent girls: the case of Lower Gwelo, Bafana ward 8 - Ndlovu, Epheanitus (Midlands State University, 2017)
Adolescent girls between the ages of 14 and 19 are at higher risk of contracting sexually transmitted infections including human immunodeficiency virus, unintended pregnancies associated with early and unsafe sexual habits. This has resulted in the researcher attempting to identify factors leading to sexual risk behaviors in Bafana ward 8 which can assist in coming with new strategies that can reduce the in withprevalence of high risky sexual practices and reductions in the spread of HIV virus among youths in rural communities.